1992
DOI: 10.1590/s0034-89101992000600008
|View full text |Cite
|
Sign up to set email alerts
|

Geographical patterns of proportionate mortality for the most common causes of death in Brazil

Abstract: SICHIERI, R. et al. Geographical patterns of proportionate mortality for the most common causes of death in Brazil. Rev. Saúde públ, S.Paulo, 26:424-30,1992. Mortality due to chronic diseases has been increasing in all regions of Brazil with corresponding decreases in mortality from infectious diseases. The geographical variation in proportionate mortality for chronic diseases for 17 Brazilian state capitals for the year 1985 and their association with socio-economic variables and infectious disease was studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
(14 reference statements)
0
7
0
3
Order By: Relevance
“…This has been discussed at historical[7], global[8], and national[9] levels, but new geomapping techniques have shown that it holds true when comparing small areas such as postal or electoral districts. The environmental and social factors conferred upon an individual through their residence in a particular area may be as important as the individual 'risk factors' where communicable disease is concerned[10].…”
Section: Introductionmentioning
confidence: 99%
“…This has been discussed at historical[7], global[8], and national[9] levels, but new geomapping techniques have shown that it holds true when comparing small areas such as postal or electoral districts. The environmental and social factors conferred upon an individual through their residence in a particular area may be as important as the individual 'risk factors' where communicable disease is concerned[10].…”
Section: Introductionmentioning
confidence: 99%
“…A possible powerful confounder in this study is the economical diversity among the cities studied. However, in a previous paper we showed that the high variation in cancer among 19 state capitals in Brazil could only be partially related to socioeconomic factors (Sichieri et al, 1992).…”
Section: Stomachmentioning
confidence: 84%
“…Low educational attainment has been consistently linked to increased risk of death, with a recent study suggesting the effect on mortality may be comparable to smoking [18,19]. Similarly poverty is a well-cited risk factor for chronic disease and premature mortality both in Brazil and across the globe [20,21]. When specifically comparing socioeconomic status and PD mortality, Yang et al found that low-income was associated to higher mortality rates while Beard et al identified higher rates in the high-income population [22,23].…”
Section: Discussionmentioning
confidence: 99%